An exploratory investigation of brain collateral circulation plasticity after cerebral ischemia in two experimental C57BL/6 mouse models. Issue 2 (February 2020) - Foddis, Marco; Winek, Katarzyna; Bentele, Kajetan; Mueller, Susanne; Blumenau, Sonja; Reichhart N, Nadine; Crespo-Garcia, Sergio; Harnett, Dermot; Ivanov, Andranik; Meisel, Andreas; Joussen, Antonia; Strauss, Olaf; et al.
Brain collateral circulation is an essential compensatory mechanism in response to acute brain ischemia. To study the temporal evolution of brain macro and microcollateral recruitment and their reciprocal interactions in response to different ischemic conditions, we applied a combination of complementary techniques (T2-weighted magnetic resonance imaging [MRI], time of flight [TOF] angiography [MRA], cerebral blood flow [CBF] imaging and histology) in two different mouse models. Hypoperfusion was either induced by permanent bilateral common carotid artery stenosis (BCCAS) or 60-min transient unilateral middle cerebral artery occlusion (MCAO). In both models, collateralization is a very dynamic phenomenon with a global effect affecting both hemispheres. Patency of ipsilateral posterior communicating artery (PcomA) represents the main variable survival mechanism and the main determinant of stroke lesion volume and recovery in MCAO, whereas the promptness of external carotid artery retrograde flow recruitment together with PcomA patency, critically influence survival, brain ischemic lesion volume and retinopathy in BCCAS mice. Finally, different ischemic gradients shape microcollateral density and size.